FAKTOR-FAKTOR YANG MEMPENGARUHI INTENSI ENTREPRENEURIAL PADA SISWA DAN MAHASISWA DI SURABAYA - Sienatra, Krimsi Budi; Padmalia, Metta (LP2M Institut Teknologi dan Bisnis Asia Malang, 2018)
This study aims to look at the early stages of the birth of a business or at the stage of conception and preparation. Specifically, the purpose of this study is to develop and test empirically the determinants of entrepreneurial intentions using entrepreneur characteristic variables such as age, education, competence, gender, job status, parental background, ability to see persuasion and persistence as a predicting factor. The sample of this research is students and students who get formal education about entrepreneurship in Surabaya city. The analysis is based on a binary logistic regression model that estimates the effect of a set of predictor variables on entrepreneurship intentions. Logistic regression results show that only the age, competence, network relations, and ability to see the opportunities that affect the intention of entrepreneurship. Out-of-the-box results are the background of the parents not impacting the entrepreneurship intentions.